Effets ergogéniques des ß2 agonistes : mode d`action et enjeux pour la lutte antidopage - Le Fur, M. A.; Sanchez, A. M. J.; Candau, R. (Movement & Sport Sciences - Science & Motricité, 2012)
ß2 adrenergic agonists are a class of drugs usually used in the treatment of asthma and other pulmonary diseases. Since 1991, increasing concern has been expressed over the widespread use of ß2 agonists among elite athletes. Indeed, it would seem that these molecules are usually used in elite competitive athletes fearing potential ergogenic doping effects and their improvement of ventilatory and muscular functions. The aim of this article is to gather the experimental data raising the effects of these molecules on aerobic and anaerobic performances, and also detail the physiological mechanisms borrowed by these substances.